Effectiveness of Nursing Counseling with Short Message Service Intervention (NC-SMSI) on Self-Care Behavior among Hypertension Patients: A Cross-Sectional Study - Rian Tasalim; M. Sobirin Mohtar; Asmadiannor Asmadiannor; R.A. Gabby Novikadarti Rahma; Takesi Arisandy (An Idea Health Journal, 2026)
Hypertension remains a major global health problem with increasing prevalence and poor self-care practices among patients. In Indonesia, particularly in Banjarmasin, decreased self-care (DSC) behaviors such as poor medication adherence, irregular physical activity, and limited blood pressure monitoring contribute to uncontrolled hypertension. Innovative nursing interventions are urgently needed to address these challenges. This study aimed to analyze the effectiveness of the Ners Counseling–Short Message Service Intervention (NC-SMSI) on improving self-care among hypertensive patients in Banjarmasin, Indonesia. The methods is a quasi-experimental study with a one-group pretest–posttest design was conducted among 30 hypertensive patients recruited using accidental sampling. The intervention combined direct nursing counseling and structured short message service reminders based on the Self-Care Deficit Nursing Theory. Self-care was measured using the DSCAI-90 instrument. Data were analyzed using the Wilcoxon Signed-Rank Test after the Shapiro–Wilk test indicated non-normal distribution. Ethical approval was obtained from the local health research ethics committee. The results is before the intervention, most respondents (53.3%) demonstrated very poor self-care, while only 3.3% achieved high levels. After the NC-SMSI intervention, 63.3% of participants reached high self-care levels, and none remained in the very poor category. The Wilcoxon signed-rank test showed a significant improvement in self-care scores (Z = –4.783, p < 0.001, r = 0.84), indicating a large effect. The conclusion is NC-SMSI effectively improved self-care behaviors among hypertensive patients. Integrating nurse counseling with mobile-based reminders offers an efficient, adaptive, and scalable model for enhancing hypertension management at the community level. This intervention holds promise for broader implementation in primary healthcare settings.